Respuesta :
(x - 5)(x^2 + 4x - 2) =
x(x^2 + 4x - 2) - 5(x^2 + 4x - 2) =
x^3 + 4x^2 - 2x - 5x^2 - 20x + 10 =
x^3 - x^2 - 22x + 10 <===
x(x^2 + 4x - 2) - 5(x^2 + 4x - 2) =
x^3 + 4x^2 - 2x - 5x^2 - 20x + 10 =
x^3 - x^2 - 22x + 10 <===
(x - 5)(x² + 4x - 2)
Distribute each term from one parenthesis to all the other terms in the other
x(x²) = x³
x(4x) = 4x²
x(-2) = -2x
-5(x²) = -5x²
-5(4x) = -20x
-5(-2) = -10
Combine all like terms:
x³ + 4x² -5x² -2x -20x -10
x³ - x² - 22x - 10 is your answer
hope this helps